Produktivitas Penangkapan Ikan Tenggiri (Scomberomorus commerson) Menggunakan Pancing Ulur di PerairanKabupaten Bintan - Jumsurizal, Jumsurizal; Nelwan, Alfa; Kurnia, Muh. (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
Mackerel is one of the main targets of hand line fishing in the  Tambelan coastal  waters, Bintan Regency. The mackerel catch data were collected by following the hand line fishing operation as many as  40 trips from December 2013 to April 2014. The productivity data of hand line fishing were calculated based on the time of fishing operations (morning, noon, afternoon). The average productivity of hand line fishing in the morning, daytime and afternoon were 0.051 kg/minutes, 0.036 kg/minutes and 0.033 kg/minutes, respectively. Handline fishing productivity in the morning was not significantly different with at the daytime, however there was a significant different in productivity between in the morning and in the afternoon. Whilst,  the fishing productivity at the daytime was not significantly different with that in the afternoon.